Digital Transformation in Education to Foster Personalized Learning - Silalahi, Jaya Wibowo Pranata; Hidayat, Dylmoon; Nathali, Christy (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This article is to explain the principles of digital transformation practices that can effectively enhance personalized learning. The article is written using a literature review method to identify various concepts, approaches, and findings from previous studies that support or challenge the role of digital technology in promoting personalized learning. The findings of this article indicate that there are four key principles to understand in digital transformation: digital innovation must specifically address students’ needs, collaboration between teachers and technology must be well-established, strong student engagement must be fostered—beyond mere compliance, and continuous evaluation must be conducted to identify challenges in technology implementation. By adhering to these principles, education can become more responsive and inclusive in meeting the unique needs of everyone, thereby enabling the effective realization of personalized learning.